Rappresentare e governare Da grande regola a tallone d'Achille del governo parlamentare - FUSARO, CARLO (Lectio Magistralis, 2015)
Political institutions must guarantee both representation and government. The peculiarity of parliamentarism lies in the fact that these two functions pass through the election of the Chamber of Parliament, to which the government is bound by a vote of confidence. This essay analyses the growing difficulties of parliamentary regimes in securing the aforementioned functions.